A HRWS SAR System Design with Multi-beam Imaging Capabilities - Castillo, J.; Younis, M.; Krieger, Gerhard (European Radar Conference (EuRAD), 2017)
Multiple channel SAR systems are a key component of next generation SAR missions. They allow the use of Digital Beamforming (DBF) techniques to overcome the classical resolution versus coverage trade-off. The High- Resolution Wide-Swath (HRWS) SAR program of the German Aerospace Center is a promising example of such a future system conception. HRWS combines a wide area illumination with a multi-channel receiver, allowing spatial resolutions in the order of one meter with 50 to 60 km swath imaging. The HRWS system design is based on planar antenna architecture combined with a transmit/receive module front-end; multiple channels are considered both in azimuth and elevation. This paper shows an extension of the HRWS system which allows enlarging the swath width to up to 200km; for this a dedicated operation mode is investigated. Further, the instrument architecture and performance assessment are described.
DLR Import::2019-04-03